2022
DOI: 10.3389/fenrg.2022.971177
|View full text |Cite
|
Sign up to set email alerts
|

Optimal performance of actuator disc models for horizontal-axis turbines

Abstract: This study analyzes actuator disc (AD) models of horizontal-axis turbines to determine optimal performance, defined as the maximum power extracted at any tip speed ratio. We use the calculus of variations to maximize rotor torque relative to the thrust without making any assumptions about the rotor loading. The torque was obtained from the angular momentum equation and the thrust from the Kutta-Joukowsky equation which depends on the circumferential velocity and tip speed ratio. The optimality requirement is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Eq. 12 gives the vortex pitch as the ratio of the blade element torque to reduced thrust, which also holds for the ideal actuator disc model of Wood and Hammam (2022), for which dT = dT*. Thus, it is not surprising that the runaway is associated with p ↓ 0.…”
Section: Figurementioning
confidence: 85%
See 2 more Smart Citations
“…Eq. 12 gives the vortex pitch as the ratio of the blade element torque to reduced thrust, which also holds for the ideal actuator disc model of Wood and Hammam (2022), for which dT = dT*. Thus, it is not surprising that the runaway is associated with p ↓ 0.…”
Section: Figurementioning
confidence: 85%
“…Their relation to the usual thrust equation is easily derived by ignoring circumferential variations and the expansion term. Wood and Hammam (2022) showed that the high−λ circumferentially uniform wakes of optimal rotors satisfy "helical symmetry:" pu = wr where p = (1 − u)/(w/r + λ) is the pitch of the helical vorticity. Applying these equations turns the right side of Eq.…”
Section: Blade Element/momentum Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…and radius as this is the only case with closed-form expressions for the induced velocities. The restriction of constant pitch is not significant as Wood and Hammam (2022) showed that the pitch is constant throughout the wake of optimal rotors as it is the ratio of torque to thrust. The restriction of constant radius is possibly more significant, but at least, the constant radius analysis captures the important features of circumferential periodicity for identical, equispaced blades.…”
Section: Woodmentioning
confidence: 99%
“…Γ is easily determined from the element lift and drag, but this determination is outside the scope of the present work. All other parameters for the induced velocities are set by the rotor geometry, except for p. It can be calculated from the blade element thrust and torque, or equivalently, from u and w immediately behind the blades (Wood and Hammam, 2022). Wood et al (2021) analyzed methods to find u and w at x = θ = 0 due to a vortex also starting at x = θ = 0.…”
Section: The Exact Equationsmentioning
confidence: 99%